A interface entre psicanálise e fonoaudiologia na intervenção de crianças com atraso na linguagem oral - Chimainski, Carina (2022)
This research proposed to discuss the oral language delay from an interdisciplinary perspective between Speech-Language Pathology and Psychoanalysis. It aimed to study and compare the effects of interdisciplinary interventions of Speech Therapy and Psychoanalysis on language development in children with language delay. The research consisted of a case study, of a qualitative nature, with longitudinal follow-up. To compose the sample, were selected 4 male children with ages between 2 and 5 years old with oral language delay. It was built two groups of therapy: G1 composed by 2 children who received only speech therapy intervention and G2 composed by 2 children who received speech therapy and psychological intervention, from a psychoanalytic approach. The data was obtained through the application of PROC (Protocol of Behavioral Observation); anamnesis interviews with parents; recordings of children's filming during moments of interaction at playing time; and, interdisciplinary dialogues between professionals. The results were analyzed psychoanalytically, as well as, qualitatively through PROC, language and symbolic play. The pre-intervention evaluations showed that the younger children, Bento (G1) and Gabriel (G2), were similar in some aspects on communicative skills and functions, cognitive development and toy level. They presented difficulties on alternation of shifts with absence in several aspects of the communicative functions. The language proved to be immediate and concrete, with no organization in play. The evaluations of the older children, Wagner (G1) and Lucio (G2), in the pre-intervention phase, also indicated similarities in their results. Lucio (G2) had more difficulty waiting for his turn at playtime and in alternation at the dialogic activity, with language referring only to the immediate and concrete situation. The post-intervention results of the cases that received interdisciplinary intervention showed a significant improvement in the different aspects listed by PROC. Although the children in G1, who received only speech therapy, showed improvement, Bento still had significant difficulties in relation to shifts and their alternation, as well in the aspects of playing. It was noted that there was no change in the category of verbal language comprehension in cases that received only speech therapy. The interdisciplinary dialogue made it possible to evolve effectively in the cases of G2. A psychoanalytic look at the cases that only received speech therapy would allow intervening with the parents, listening to their phantasmagorical speech and working with the children on their questions about the presented problem.